Nilai Tambah dan Sikap Konsumen Produk Brownies Berbahan Baku Tepung Ubi Kayu Tinggi Protein - Zukryandry Zukryandry; Annisa Fitri; Beni Hidayat (Fakultas Pertanian, Universitas Timor, 2021)
The added value of high protein cassava flour to brownies shows the potential of the product to be developed. Producers of brownies made from high protein cassava flour must be oriented towards consumer interests, namely producing products that are in accordance with consumer demands and desires. This research aimed to analyze the added value of high protein cassava flour as a raw material for making steamed brownies and to analyze consumer attitudes towards steamed brownie products made from high protein cassava flour. This study used cross section data from high-protein cassava flour brownies and 25 consumers. The method of value added analysis used is the Hayami method and fishbein for analysis of consumer properties. The results showed that the added value of brownies made from high protein cassava flour: Rp.29.356 kg with a value added ratio of 49.92 high category. Overall consumer attitudes are positive for high protein cassava flour brownies and the attributes that are considered for purchasing high protein cassava flour brownies include taste and price.